Interannual dynamics of dissolved carbon and nitrogen forms in habitats of coastal plant communities (Peter the Great Bay, Sea of Japan) - E. V. Levchenko; L. I. Sabitova; V. A. Parensky; V. I. Zvalinsky (Известия ТИНРО, 2023)
The interannual dynamics of dissolved forms of carbon and nitrogen in the habitat zone of marine coastal plant communities has been studied in the waters of Peter the Great Bay, Sea of Japan/East Sea, with different levels of eutrophication, in summer. An analysis of the obtained data based on selection of functional models by the statistical methods has shown that the interannual dynamics in the contents of total dissolved nitrogen and carbon, as well as dissolved organic and inorganic carbon, have a nonlinear pattern. The hydrochemical regime of the water areas under study is discussed and their biological productivity assessed on the basis of the model trends. High productivity was recorded from coastal waters of Amur and Ussuri Bays characterized by different levels of eutrophication (high in Amur Bay and low in Ussuri Bay). This result indicates that coastal waters with both high and low eutrophication levels can be highly productive. The study of the interannual dynamics of variations in the dissolved organic and inorganic carbon content allows an assumption that the intensity of production and destruction processes is higher in coastal biocenoses of Ussuri Bay, while the activity of the biological carbon pump in the coastal waters of Amur Bay is decreased.